Assessment of cardiac allograft systolic function by global longitudinal strain: From donor to recipient. Issue 5 (8th April 2017) - DeVore, Adam D.; Alenezi, Fawaz; Krishnamoorthy, Arun; Ersboll, Mads; Samsky, Marc D.; Schulte, Phillip J.; Patel, Chetan B.; Rogers, Joseph G.; Milano, Carmelo A.; Velazquez, Eric J.; Khouri, Michel G.
Abstract: Background: Cardiac allografts are routinely evaluated by left ventricular ejection fraction (LVEF) before and after transplantation. However, myocardial deformation analyses with LV global longitudinal strain (GLS) are more sensitive for detecting impaired LV myocardial systolic performance compared with LVEF. Methods: We analyzed echocardiograms in 34 heart donor‐recipient pairs transplanted at Duke University from 2000 to 2013. Assessments of allograft LV systolic function by LVEF and/or LV GLS were performed on echocardiograms obtained pre‐explanation in donors and serially in corresponding recipients. Results: Donors had a median LVEF of 55% (25th, 75th percentile, 54% to 60%). Median donor LV GLS was −14.6% (−13.7 to −17.3%); LV GLS was abnormal (ie, >−16%) in 68% of donors. Post‐transplantation, LV GLS was further impaired at 6 weeks (median ‐11.8%; −11.0 to −13.4%) and 3 months (median −11.4%; −10.3 to −13.9%) before recovering to pretransplant levels in follow‐up. Median LVEF remained ≥50% throughout follow‐up. We found no association between donor LV GLS and post‐transplant outcomes, including all‐cause hospitalization and mortality. Conclusions: GLS demonstrates allograft LV systolic dysfunction in donors and recipients not detected by LVEF. The clinical implications of subclinical allograft dysfunction detected by LV GLS require further study.